A foglalkozásnévi eredetű családnevek típusa a magyar családnevek rendszerében Egy történeti névtipológiai vizsgálat tanulságai [Occupational names in the system of Hungarian family names Outcomes of a typological analysis of historical names] - Slíz, Marianna Ilona (Névtani Értesítő, 2016)
Occupational names can be regarded as one of the most characteristic types of Hungarian family names: 10 out of the 20 most frequent family names in the stock of contemporary surnames belong to this category. The paper explores the history of this type of Hungarian family names, with special emphasis on its social distribution and also its change in frequency in relation to other family name types. Furthermore, the survey examines the role of occupational family names in official family name changes in Hungary in the past; investigates the social-historical and political background for choosing occupational family names when changing one’s surname; and also mentions some invented occupational family names. Finally, the paper deals with the question of social discrimination based on family names in present day society, which may lead to the change of certain occupational family names for more „neutral” ones.